Evaluating experiences and knowledge of developmental dysplasia of the hip management among healthcare professionals in Medina, Saudi Arabia - Alnefaie, Zayed M.; Almutairi, Abdulrahman S.; Alquliti, Waleed K.; Banjar, Morad A.; Al-Samiri, Samer F.; K., Alqelaiti Majed Wasel; Hamed, Rayan A.; Shahat, Khaled A. (International Journal of Research in Orthopaedics, 2026)
Background: Developmental dysplasia of the hip (DDH) is a leading pediatric orthopedic condition with serious long-term consequences if not identified and treated early; despite the preventability of its complications, delayed diagnoses remain common in Saudi Arabia, highlighting the need to assess healthcare providers’ knowledge and practices. This study aimed to evaluate the knowledge, experiences, and clinical practices related to DDH management among healthcare professionals in Medina, Saudi Arabia. Methods: A cross-sectional design was used, involving 123 healthcare professionals who completed a validated self-administered questionnaire assessing knowledge of DDH risk factors, diagnosis, management, and screening practices, and the data were analyzed using descriptive statistics and chi-square tests to examine associations between demographic variables and knowledge levels. Results: The results showed a mean knowledge score of 54.62% (±20.28%), with 44.7% of participants classified as having poor knowledge, 36.6% moderate knowledge, and only 18.7% demonstrating good knowledge, while no statistically significant associations were found between knowledge level and occupation, years of experience, workplace setting, or number of DDH cases encountered. Screening practices were inconsistent, as only 30.1% always examined infant hips and 46.3% did not perform assessments at every well-baby visit; although 60.2% relied on clinical examination for diagnosis, 42.3% reported a lack of access to ultrasonography, and 52% had not received formal training in DDH screening. Conclusions: Despite these gaps, 86.2% of participants agreed that implementing standardized protocols would be beneficial, and overall, the findings indicate a clear deficiency in knowledge and inconsistency in screening and management practices, emphasizing the need for targeted training programs and standardized guidelines to enhance early detection and improve patient outcomes.